84 Shaheen palliative care project, Pakistan. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Bilal, Sobia; Ali, Maimoona; Mudassir, Sadaf; Naeem, Awais; Hussain, Adeel Basharat; Khan, Jalil; Abbas, Qamar; Butt, Mohammad Ayyaz
Abstract : Background: Shaheen Palliative care project team aim to develop a training and service oriented programme. The team help provide compassionate palliative care for patients living with a life-limiting illness and their families, through physical, emotional, spiritual, psychological and social support. There are no current palliative care services in hospitals or communities for the people of Pakistan. The aim of the team is to equip and train Pakistani healthcare workers with the essential knowledge and skills to able to provide the best quality palliative care aswell as public awareness of palliative medicine. Methods: A service evaluation about palliative care services in Pakistan. Two surveys were sent, one to all grades of doctors at two hospital sites in Peshawar, Pakistan and the second to members of the general public. The data was then analysed using Excel. Results: There were 60 respondents, in total, to both the surveys. 95% were involved in care of the terminally ill with only 20% of them being confident in managing patients with a life limiting disease. 85% said they did not have access to necessary drugs for pain control in terminally ill patients. 70% thought hospice was synonymous with palliative care. 100% of respondents thought there is a need for palliative care services in Pakistan. Conclusions: This evaluation was undertaken to help develop a training and service-oriented palliative care programme for people of Pakistan working towards specialist palliative care services. The Shaheen Palliative care team have set up the first Palliative Care Postgraduate certificate at Khyber University, October 2019 and the National University of Medical Sciences, Rawalpindi, shall also be starting Post Graduate Palliative Care Certificate from end of 2020. The multi-professional international team are leading the way in developing new services and palliative medicine education in Pakistan for both the healthcare professional and the public.